Nutrition and origin of US chain restaurant seafood. Issue 6 (10th March 2021) - Love, David C; Turvey, Catherine; Harding, Jamie; Young, Ruth; Ramsing, Rebecca; F Tlusty, Michael; Fry, Jillian P; Nguyen, Ly; Asche, Frank; Nussbaumer, Elizabeth M; Thorne-Lyman, Andrew L; Bloem, Martin
ABSTRACT: Background: Seafood has a nutritional profile that can be beneficial to human health, which gives it a role to play in healthy diets. In addition, because its production and harvesting can have fewer environmental impacts than some forms of animal protein, it can contribute to sustainable diets. However, the positive health and environmental outcomes are not guaranteed—they depend on how seafood is prepared and served and whether it is sourced from sustainable fisheries and aquaculture industries. Objectives: We examined the availability and nutritional attributes of seafood meals at chain restaurants in the United States. We assessed nutritional attributes by store type and geography. We also assessed menu labeling for species, production methods, and origin. Methods: The study population was 159 chain restaurants with 100, 948 branch locations in the United States. Data were harvested from online restaurant menus, and the nutritional profile of seafood meals was calculated. Results: The average seafood menu item provides up to 49–61% of the total daily limit of saturated fat, 65% of the total daily limit of sodium, and 58–71% of total daily protein requirement for adult men and women. Restaurant chains located in the Deep South and Ohio River Valley, and casual dining chains nationally, carry seafood meals with more total calories and saturated fat per 100 g than other regions or chain types. Most menu items did not list origin or production methods, which is information that would help consumers make informed decisions. Conclusions: The added ingredients and cooking methods used at chain restaurants can attenuate the health benefits of seafood. We recommend reformulating menus to reduce portion sizes, total calories, added fat, and sodium content per meal and to improve consumer-facing information about origin and production methods.